Review of Student Service-Learning Program in the Early Period of the Higher Education System in Indonesia - Wahyuni, Andi Sri (UI Scholars Hub, 2023)
This study investigates the early formation and historical development of student service-learning in Indonesia from a global context. Employing a qualitative approach, it utilizes archival research methods for examining the inception of student service- learning, a community empowerment program conducted by the students in the country. It analyzed international documents sourced from Google Books archives, which are available through various online platforms and supplemented by the use of Google Ngram Viewer. The findings indicate that the concept of student service- learning was introduced in Indonesia during the academic year 1971/1972 and adopted by numerous universities before it became mandatory for end-year students starting from 1973 to 1974. This study represents the inaugural archival investigation that revealed that the local community warmly welcomed the arrival of students at the time because their contributions significantly improved societal well-being. Students benefited from direct experiential learning with the community, while the community received assistance and empowerment through resources provided by the universities. Furthermore, the study highlights that in discussions, especially after the establishment of Kuliah Kerja Nyata (KKN) or service-learning as a mandatory program in 1974, numerous documents (eight in 1975 and twelve in 1976) cited KKN as a reference in the international arena. This recognition positions KKN as an exemplary service- learning program on a global scale.